Prevalence of Hepatitis C Virus Infection among Hemodialysis Patients at a Tertiary-Care Hospital in Mexico City, Mexico - Méndez-Sánchez, Nahum (American Society for Microbiology, 2004)
We determined the prevalence of hepatitis C virus (HCV) in hemodialysis patients by antibody testing and HCV RNA determination by PCR. A total of 149 patients with kidney failure with replacement therapy were tested. The prevalence of anti-HCV was 6.7% (10 of 149 patients), and viremia was detectable in 8 of 149 (5%) patients. Three of 149 patients (2%) were anti-HCV negative with detectable HCV RNA.